PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS KARYAWAN NON MEDIS RS ISLAM SITI KHADIJAH PALEMBANG) - Riski Damayanti; agustina hanafi; afriyadi cahyadi (JEMBATAN, 2018)
This study aims to know how much the influence of job satisfaction on the Employees performance of Non Medical Employees of Rumah Sakit Islam Siti Khadijah Palembang. Job satisfaction is a happy emotional state or a positive emotion that comes from an assessment of work or a person's work experience that can effect the performance of employees, either directly or indirectly. This research is descriptive research with quantitative approach. The population used was 40 respondens. The result of this study indicate that there is the influence between the job satisfaction on the Employees performance of Non Medical Employees of Rumah Sakit Islam Siti Khadijah Palembang. This was proved by t-count  the percentage of (2,309) > t-table (2,024) with a significance of 0,026 smaller than ? 0,05 (0,026 < ? 0,05).Keywords: Job Satisfaction, Performance